Resurgence of measles virus infection in an eliminated country, Sri Lanka - Merennage Anusha Yasanthi Fernando; Gankandage Prabhath Chathuranga; Kaanthaka Gunaradha Abeygunasekara; Dedunu Dias Weligamage; Janaki Indira Abeynayake (Asian Pacific Journal of Tropical Medicine, 2024)
To describe the situation of measles in Sri Lanka from May to November, 2023 and to define the role of virology laboratory towards case confirmation and epidemiological and genetic characterization of the outbreak. This retrospective study analyzed all samples tested for measles from 1st of May to 30th of November, 2023 at National Measles Rubella Laboratory, Sri Lanka. According to the World Health Organization (WHO) algorithm, serum and oropharyngeal/nasopharyngeal swabs were tested with WHO recommended kits for anti-measles IgM and measles virus specific RNA, respectively. Selected RNA positive samples were sequenced at reference laboratory, India. Analysis of sequencing data and construction of phylogenetic tree were carried out at National Measles Rubella Laboratory. Data was analyzed using descriptive statistics. Of the total 1132 serum samples and 497 oropharyngeal/nasopharyngeal swabs from 1326 patients, 657 (49.5%) patients were confirmed as measles by anti-measles IgM, measles virus specific RNA or both. Males (55.6%, n=365) and the age group from >20 to ≤30 years (33.0%, n=217) predominated positive patients. All provinces reported measles positive cases. All samples sequenced (100%, n=42) were genotype D8 with 95.2% (n=40) bearing Victoria. Australia origin. We described resurgence of measles in an eliminated country, confirming the genotype to be D8, one of the two genotypes currently circulating globally. Further, the study strongly convinced the importance of a strengthened virological surveillance system in an eliminated country, despite its eliminated status.